T113. The changes in motor cortex localisation and organisation in motor eloquent tumorous brain lesions detected by navigated transcranial magnetic stimulation. (May 2018) - Holeckova, Irena; Vales, Jiri; Mracek, Jan; Rihanek, Petr; Moucek, Roman; Mautner, Pavel; Priban, Vladimir
Abstract : Introduction: Navigated transcranial magnetic stimulation (nTMS) is non invasive method to map the motor cortex including primary motor cortex (PrG - precentral gyrus) and premotor areas (PMa). This study aimed to investigate whether tumorous brain lesion induce a change in motor cortex localization or organisation investigated by nTMS. Methods: We enrolled 10 patients with intraaxial motor tumor (gliomas). All patients underwent preoperative navigational MRI folowed by nTMS. Both lesional and non lesional hemispheres were stimulated. MEPs were recorded by EMG. The measured muscle was APB. MEPs latency for each positive stimulation point was measured. The surface of positive stimulation areas on the cortex were calculated for both hemispheres and results were compared. Results: The positive MEPs responses were registered from PrG as well as from PMa with different latencies. There were mosaic distribution of short and long latencies of MEPs responses without dependence on the location in the PrG or PMa in both hemispheres. The positive motor area distributions were significantly larger from lesional than for non lesional hemisphere for both PrG and PMa areas (PrG lesional vs. non lesional surface = 947 mm 2 vs. 393 mm 2, PMa lesional vs. non lesional surface = 620 mm 2 vs. 545 mm 2 ). Conclusion: The intraaxial motor eloquent tumors induce changes in motor cortex. The motor areas spread widely in the anterior-posterior direction in lesional hemisphere. The localisation short latencies found in PMa suggesting for detection of primary motor areas outside the PrG. This study was supported by the Charles University Research Fund Progress Q 39.